Voices Welcomes Interviews - Stachyra, Krzysztof (Voices: A World Forum for Music Therapy, 2009)
We would like to invite and encourage you to join the process of creating our common journal. Every of us can support the development of Voices by letting us know and interviewing people whose work inspires you and shows you the power of music and musictherapy.